Chemical analysis and consumer preference of selected poultry egg types in Zaria, Nigeria (2013)
The chemical composition, cholesterol content and consumer evaluation of eggs from Japanese quails, guinea fowls, local chickens, and exotic chickens (Isa Brown) were determined. A total of one hundred eggs, twenty five from each of species were used to determine the chemical composition, cholesterol content and sensory evaluation (Five eggs for chemical composition, cholesterol content and twenty for sensory). On a dry matter basis, the local chicken had a significantly (P<0.05) lower value of 23.20% than other species. The exotic chicken ranked highest with a mean value of38.39%. The mean values recorded for ether extract showed no significant difference (P>0.05) amongst the four species. The ash content of the local chicken was significantly (P<0.05) lower (4.33%)) than that of Japanese quails, guinea fowl and exotic chickens with values of4.84, 4.87 and 5.15 per cent, respectively. Values obtained for the nitrogen free extract also showed the local chicken to be significantly (P<0.05) lower (47.54%) than the other species whose values ranged between 51.39 - 52.06%. The exotic chicken had a significantly higher cholesterol value of243.8 mg/dl while the values for the guinea fowl and the local chicken did not significantly (P>0.05) differ while the Japanese quail eggs had the least cholesterol value of 80.60 mg/dl. Smell and texture were not significantly (P>0.05) influenced by egg type however the guinea fowl and local chicken eggs were the most preferred in terms of colour and the quail with respect to taste. The lower cholesterol content of quail eggs perhaps gave it the potential of topping the consumers list of preference and wider acceptability. It is also evident that consumer’s preference for one egg type over others might not be absolutely based on nutritional considerations but on psychological perceptions.